Leaching of Fluoride from Biotite Mica in Soil: Implications for Fluoride in Shallow Groundwater. (8th February 2012) - Kularatne, K. U. K. S.; Pitawala, H. M. T. G. A.
Abstract : Leaching ofF - from biotite was investigated at room temperature by performing a series of short-term leach tests. The leaching ofF - from biotite structure strongly depends on its weathering stage. Results of this study suggest that high concentration ofF - is leached from highly weathered biotite, compared to fresh biotite. Results of dissolution experiments confirm that the organic acids in soil promote the leaching ofF - from biotite compared to inorganic acids. Citric acid which is a week organic acid enhances leaching ofF - from biotite structure compared to strong inorganic acid HNO3, independent of the weathering stage of biotite. Strong positive correlation between K + and Fe 2+ withF - in biotite treated with citric acid suggests thatF - readily leachs into the solution through an ionic exchange and complex formation. Organic acids involve sorption and complex formation processes leading to release ofF - into the solution. Our studies suggest that in the presence of organic acidsF - is leached readily into water percolating through the soil. Therefore, shallow groundwater replenished by the water table may achieve highF - concentrations by this leaching process.